2018
DOI: 10.1088/1361-648x/aaa944
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of genome and structural ions in preventing viral capsid collapse during dehydration

Abstract: Even though viruses evolve mainly in liquid milieu, their horizontal transmission routes often include episodes of dry environment. Along their life cycle, some insect viruses, such as viruses from the Dicistroviridae family, withstand dehydrated conditions with presently unknown consequences to their structural stability. Here, we use atomic force microscopy to monitor the structural changes of viral particles of Triatoma virus (TrV) after desiccation. Our results demonstrate that TrV capsids preserve their g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…The hydrated native TGEV particles’ height ranged from ~30 to ~140 nm ( Figure 1 G), which highlights the pleomorphism of TGEV as described for other CoVs [ 51 , 52 , 53 , 54 ], and resulted into two main populations, one at ~43 nm and the highest peak, at ~75 nm ( Figure S1B ). When virions were dehydrated, they lost around 40% of their height, as shown in previous studies [ 55 ], and also presented a smooth surface. In the case of rehydrated particles, they seemed to recover their initial height ( Figure 1 D), although their surface presented a roughness far different from the initial smooth condition ( Figure 1 B).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The hydrated native TGEV particles’ height ranged from ~30 to ~140 nm ( Figure 1 G), which highlights the pleomorphism of TGEV as described for other CoVs [ 51 , 52 , 53 , 54 ], and resulted into two main populations, one at ~43 nm and the highest peak, at ~75 nm ( Figure S1B ). When virions were dehydrated, they lost around 40% of their height, as shown in previous studies [ 55 ], and also presented a smooth surface. In the case of rehydrated particles, they seemed to recover their initial height ( Figure 1 D), although their surface presented a roughness far different from the initial smooth condition ( Figure 1 B).…”
Section: Resultssupporting
confidence: 79%
“…In fact, this behavior was repeated in the comparison of dehydrated native and dehydrated PFA-fixed particles, where the non-fixed ones had a smooth surface ( Figure 1 C) and the fixed ones had a rough surface ( Figure 1 F). As for the height, dehydration of unfixed virions produced a clear decrease in its mean height, as has been observed in other viruses, whose collapsed structures had lost water and the proteins had been partially denatured [ 55 ]. Further rehydration of native TGEV particles ( Figure 1 D) recovered the particles’ height ( Figure 1 G) although with some rugosity on the surface that could correspond to the denatured proteins in the membrane.…”
Section: Discussionmentioning
confidence: 56%
“…First, ions are integrated into the structure of viral capsids, and it is known that such 'structural ions' are important for preventing capsid collapse during the desiccation of the Triatoma virus (TrV). 81 Presumably the same applies more generally to other viruses. Secondly, we may expect that biopolymers, lipids and salts could help retain residual moisture and therefore change the local absolute humidity (mass of water per unit volume of air).…”
Section: Perspective Soft Mattermentioning
confidence: 96%
“…TrV is exposed to alkaline pH in the insect intestines, and excreted in large amounts in the insect feces, from where virions can be isolated and subjected to structural analyses. Such analyses showed that under extreme natural conditions, such as drying, the particles do not disintegrate but are held intact by the internal genome, which prevents capsid collapse (Martin-Gonzalez et al, 2018). In addition, the virion responds to changes in pH.…”
Section: Chapter 9: Proton Diode and Alkaline Ph In Insect Virusesmentioning
confidence: 99%